Detection and circulation of hepatitis B virus immune escape mutants among asymptomatic community dwellers in Ibadan, southwestern Nigeria (2015)
In 2012, the first Nigerian Hepatitis B Virus (HBV) immune escape mutant (IEM) case was detected in a pregnant woman in southwestern Nigeria. Consequently, this study was designed to investigate the presence and possible circulation of IEMs amongst asymptomatic community dwellers in southwestern Nigeria. Methods: Blood specimens collected from 438 asymptomatic community dwellers were screened for HBsAg using ELISA technique. Subsequently, the S-gene was amplified in HBsAg positive samples by a nested PCR protocol, and amplicons sequenced. Isolates were then subtyped by amino acid residues at positions 122, 127, 134 and 160, and genotyped by phylogenetic analysis. Results of the 31 (7.08%) samples positive for HBsAg, the _408 bp Sgene fragment was successfully amplified and sequenced in 27. Samples obtained from 4 patients could not be amplified due to low titres. Sequence data from only 15 of the isolates could be analysed further as eight of the remaining 12 had multiple peaks while the rest three showed no similarity to any HBV gene when subjected to BLAST analysis. Thirteen of the 15 isolates were identified as genotype E. Eleven of which were subtyped as ayw4 while the remaining two could not be subtyped due to sR122Q/P substitutions. The last two isolates that could not be genotyped and subtyped had other mutations in the ‘‘a’’ determinant associated with IEMs. Conclusions: This study confirmed presence and circulation of HBV IEM in Nigeria, the country’s inclusion in the genotype E crescent, and the value of phylogenetic analysis in HBV identification.